A water-resistant room temperature phosphorescence gradient enhancement material and preparation method thereof
By using acrylamide copolymerization, cucurbit 7 complexing and formaldehyde crosslinking in pure organic room temperature phosphorescence materials, water-resistant room temperature phosphorescence gradient reinforcement materials were prepared, which solved the problem that the material was difficult to emit phosphorescence in aqueous solution, and achieved the goal of High-efficiency phosphorescence emission and stability in water.
Patent Information
- Application Number
- CN202410496461.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-24
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-04-24
AI Technical Summary
It is difficult for existing pure organic room temperature phosphorescent materials to achieve phosphorescence emission in aqueous solutions, and their application is limited by high concentrations of dissolved oxygen and rapid molecular movement.
By preparing water-resistant room temperature phosphorescence gradient reinforcement materials, three constraint methods are adopted: phosphorescence molecules form copolymers with acrylamide, complex with cucurbitol 7, and crosslinking with formaldehyde to form a crosslinking structure to improve the stability and water resistance of the material. sex.
Effective phosphorescence emission in water is achieved, the phosphorescence lifetime and stability of the material is improved, the phosphorescence emission performance can be maintained in aqueous solution, and phosphorescence can still be stimulated after soaking in water.
Smart Images

Figure CN118271516B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of organic phosphorescent materials, and in particular to a water-resistant room temperature phosphorescent gradient enhancement material and a preparation method thereof. Background Art
[0002] At present, pure organic room temperature phosphorescent (RTP) materials used in the optoelectronic field are a research hotspot in the field of organic electronics. RTP materials do not contain heavy metals, and phosphorescence can be observed at room temperature. Compared with organic metal phosphorescent materials, they are inexpensive, safe and non-toxic, and have broad application prospects. By effectively controlling the quantum efficiency, luminescence lifetime and color of RTP materials, or generating RTP emission with stimulus response characteristics, there is great potential for development in various application fields such as optical encryption, organic light-emitting diodes, ion detection, and sensing. There is great potential for development in various application fields such as optical encryption, organic light-emitting diodes, ion detection, and sensing.
[0003] At present, RTP materials are mainly prepared by copolymerizing pure organic room temperature phosphorescent monomers with acrylamide, acrylic acid, styrene sulfonic acid / sodium and vinyl pyridine, etc., which have strong room temperature phosphorescent luminescence characteristics and long phosphorescence life. For example, the patent with announcement number CN109306034B discloses a method for preparing a pure organic long-life room temperature phosphorescent polymer material in an amorphous state without heavy atoms. On the basis of an aromatic ring with an oxygen-containing functional group, a pure organic polymer material with room temperature phosphorescent luminescence characteristics is obtained by simple copolymerization with acrylamide. However, the current RTP material can only emit phosphorescence under dry conditions, and it is difficult to achieve phosphorescence emission in aqueous solution; this is because the high concentration of dissolved oxygen and rapid molecular motion in the aqueous solution cause the phosphorescence quenching of the material, resulting in its practical application in aqueous solution being limited.
[0004] How to prepare waterproof RTP materials and achieve effective RTP emission in aqueous solution is one of the great challenges in this field. Summary of the invention
[0005] The present application provides a water-resistant room temperature phosphorescent gradient enhancement material and a preparation method thereof, and prepares a waterproof RTP material, aiming to solve the problem that the existing RTP material is difficult to achieve phosphorescent emission in aqueous solution.
[0006] In order to achieve the above objectives, the present application adopts the following technical solutions.
[0007] In a first aspect of the present application, a method for preparing a water-resistant room temperature phosphorescent gradient enhancement material is provided, comprising:
[0008] Step 1, preparing phosphorescent molecular monomers;
[0009] Step 2, dissolving acrylamide in a polar solvent, adding an initiator and a phosphorescent molecular monomer, and copolymerizing under a nitrogen atmosphere; collecting a solid to obtain an acrylamide-based copolymer;
[0010] Step 3, using cucurbituril or cyclodextrin as the main body and the phosphorescent molecule in the acrylamide copolymer as the guest, performing complexation at 40-50° C. to obtain a complex;
[0011] Step 4, preparing an aqueous solution of the complex, adding a crosslinking agent to carry out a crosslinking reaction at 50-70° C., and precipitating the reaction solution with a precipitant to obtain a water-resistant room temperature phosphorescent gradient enhancement material.
[0012] In some embodiments, the chemical structure of the phosphorescent molecule monomer is as shown in formula (1):
[0013]
[0014] Wherein, R is carboxyl, boric acid, amino, cyano, methyl, trifluoromethyl or ethyl formate.
[0015] In some embodiments, the preparation method of the phosphorescent molecular monomer is:
[0016] The phenylpyridine derivative is dissolved in a polar solvent, 4-vinylbenzyl chloride is added, and the mixture is heated to 70-90° C. for reaction, and the liquid phase is collected and recrystallized with a non-polar solvent to obtain a phosphorescent molecular monomer.
[0017] The chemical structure of the phenylpyridine derivative is shown in formula (2):
[0018]
[0019] Wherein, R is carboxyl, boric acid, amino, cyano, methyl, trifluoromethyl or ethyl formate.
[0020] In some embodiments, the molar ratio of the phosphorescent molecular monomer to acrylamide is 1:(500-2000).
[0021] In some embodiments, the initiator is azobisisobutyronitrile, azobisdimethylvaleronitrile, ammonium persulfate, potassium persulfate, or benzoyl peroxide;
[0022] The polar solvent is N,N-dimethylformamide, ethanol or acetone.
[0023] In some embodiments, the molecular weight of the acrylamide-based copolymer is 3,000 to 20,000.
[0024] In some embodiments, the cucurbituril is cucurbituril 7 or β-cyclodextrin;
[0025] The molar ratio of the cucurbituril 7 or β-cyclodextrin to the phosphorescent molecule is (1:3) to (5:3).
[0026] In some embodiments, the cross-linking agent is formaldehyde, and the amount of formaldehyde used is 0.3-0.8% of the molar amount of the complex.
[0027] In some embodiments, the cross-linking agent is formaldehyde, and the amount of formaldehyde used is 3-8% of the molar amount of the complex.
[0028] The second aspect of the present application provides a water-resistant room temperature phosphorescent gradient enhancement material prepared by the above preparation method.
[0029] Compared with the prior art, the beneficial effects of this application are:
[0030] The present application achieves step-by-step enhancement of phosphorescence through three different constraint methods. The primary constraint is to form an acrylamide-based copolymer through the phosphorescent molecules and acrylamide to emit phosphorescence; the phosphorescent molecules in the acrylamide-based copolymer are then complexed with cucurbituril 7 to achieve the second constraint, so that the phosphorescence lifetime is enhanced; finally, the complex is cross-linked with formaldehyde as the third constraint, so that the phosphorescence lifetime of the room temperature phosphorescent material is further enhanced, and three different intensities of emission of the phosphorescent molecules are achieved.
[0031] In the water-resistant room temperature phosphorescent gradient enhancement material of the present application, polyacrylamide and formaldehyde form a cross-linked structure through covalent bonds, and the amide groups between molecules are cross-linked into an insoluble gel through methylene groups. The water-resistant room temperature phosphorescent gradient enhancement material of the present application can effectively hinder molecular motion through covalent bond interactions and host-guest complexation, improve the rigidity of phosphorescent molecules and thus inhibit their non-radiative decay, and the cross-linked structure can shield the quencher, thereby producing efficient polymer room temperature phosphorescence emission. The cross-linked structure in the present application enhances the stability and water resistance of the RTP material, and the degree of cross-linking of the RTP material can be changed by increasing the amount of cross-linking agent. The highly cross-linked product can achieve phosphorescence emission in water, and it is still not completely swollen after being immersed in an aqueous solution for 30 minutes, and can still stimulate phosphorescence, and an obvious afterglow can be seen. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0033] Figure 1 Phosphorescence performance diagram of the acrylamide-based copolymer, complex, phosphorescent material 1 prepared in Example 1 and phosphorescent material D1 prepared in Comparative Example 1;
[0034] Figure 2 The actual pictures of the phosphorescent material 2 prepared in Example 2 before and after drying;
[0035] Figure 3 This is a graph showing the phosphorescence performance of the phosphorescent material 2 prepared in Example 2;
[0036] Figure 4 This is a graph showing the phosphorescence performance of phosphorescent material 2 prepared in Example 2 in water. DETAILED DESCRIPTION
[0037] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0038] In the following description of this embodiment, the terms "include", "comprising", "having" and "containing" are all open terms, meaning including but not limited to.
[0039] In the following description of this embodiment, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.
[0040] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0041] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0042] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0043] Those skilled in the art will appreciate that the numerical ranges in the embodiments of the present application are to be construed as specifically disclosing each intermediate value between the upper and lower limits of the scope. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present application. The upper and lower limits of these smaller ranges may be independently included or excluded in the scope.
[0044] Unless otherwise specified, the technical / scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which this application belongs. Although this application only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of this application. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0045] In a first aspect, the present application provides a method for preparing a water-resistant room temperature phosphorescent gradient enhancement material, comprising:
[0046] Step 1, preparing phosphorescent molecular monomers;
[0047] In the present application, the chemical structure of the phosphorescent molecule monomer is shown in formula (1):
[0048]
[0049] Wherein, R is a group that can form a complex with cucurbituril 7, and R can be selected from carboxyl, boric acid, amino, cyano, methyl, trifluoromethyl or ethyl formate; R is preferably carboxyl, boric acid or amino. In this application, the phosphorescent molecule is referred to as PHC.
[0050] The phosphorescent molecular monomer is prepared by the following method:
[0051] The phenylpyridine derivative is dissolved in a polar solvent, 4-vinylbenzyl chloride is added, and the mixture is heated to 70-90° C. for reaction, and the liquid phase is collected and recrystallized with a non-polar solvent to obtain a phosphorescent molecular monomer.
[0052] The chemical structure of the phenylpyridine derivative is shown in formula (2):
[0053]
[0054] Wherein, R is a group that can be complexed with cucurbituril 7, and R can be selected from carboxyl, boric acid, amino, cyano, methyl, trifluoromethyl or ethyl formate; R is preferably carboxyl, boric acid or amino.
[0055] The polar solvent is anhydrous acetonitrile or methanol, preferably anhydrous acetonitrile, and the non-polar solvent is anhydrous ether or chloroform.
[0056] Step 2, dissolving acrylamide in a polar solvent, adding an initiator and a phosphorescent molecular monomer, and copolymerizing under a nitrogen atmosphere; collecting the solid to obtain an acrylamide-based copolymer; the chemical reaction formula is as follows:
[0057]
[0058] Wherein, acrylamide, initiator and phosphorescent molecular monomer undergo heterogeneous solution polymerization in the polar solvent to obtain an acrylamide-based copolymer. In an embodiment of the present application, the polar solvent is N,N-dimethylformamide, ethanol or acetone, preferably N,N-dimethylformamide; the initiator is azobisisobutyronitrile, azobisdimethylvaleronitrile, ammonium persulfate, potassium persulfate or benzoyl peroxide, preferably azobisisobutyronitrile.
[0059] In the present application, the molar ratio of the phosphorescent molecular monomer to acrylamide is preferably 1:(500-2000), more preferably 1:1000.
[0060] The copolymerization temperature is 60-70°C, and the copolymerization time is 12-24 hours. After the copolymerization, the reaction liquid is filtered to collect the solid copolymer.
[0061] In the present application, it is preferred that the solid copolymer is dissolved in deionized water and dialyzed to cut off the copolymer with a molecular weight of 3000 to 20000 to obtain the acrylamide-based copolymer.
[0062] Step 3, using cucurbituril or cyclodextrin as the main body and the phosphorescent molecules in the acrylamide copolymer as the guest, complexing is carried out at 40-50° C. to obtain a complex. The chemical reaction is shown in the following formula:
[0063]
[0064] In the present application, cucurbituril or cyclodextrin is used as the main body to form a host-guest complex with the phosphorescent molecules in the acrylamide-based copolymer. Among them, cyclodextrin is preferably β-cyclodextrin, and cucurbituril is preferably cucurbituril 7. Specifically, the cavity of cucurbituril needs to match the size of the phosphorescent molecule to achieve the best complexation effect. If the cavity is too large, such as cucurbituril 8, the phosphorescent molecule cannot be perfectly complexed; if the cavity is too small, such as cucurbituril 6, the phosphorescent molecule cannot enter it for complexation. This application uses cucurbituril 7, which has a moderate cavity size and can just complex the phosphorescent molecules. Among the three, it has the best ability to inhibit the vibration of the phosphorescent molecules, so that its phosphorescent performance is optimized.
[0065] In the present application, the molar ratio of cucurbituril 7 to the phosphorescent molecule is preferably (1:3) to (5:3), and the molar ratio of cucurbituril 7 to the phosphorescent molecule is more preferably 1:1.
[0066] In the present application, the complex is mainly composed of polyacrylamide, the molar content of which is 99.9%, and it also contains a small amount of phosphorescent molecules and cucurbituril 7, the molecular weight of which is calculated to be 72.53.
[0067] Step 4, prepare the complex into an aqueous solution, add a crosslinking agent to carry out a crosslinking reaction at 50-70°C, and precipitate the reaction solution with a precipitant to obtain a water-resistant room temperature phosphorescent gradient enhancement material. The chemical reaction is shown in the following formula:
[0068]
[0069] Here, PHC stands for phosphorescent molecule.
[0070] In the present application, the precipitant is selected from alcohols, tetrahydrofuran or diethyl ether, preferably alcohols, and particularly preferably methanol.
[0071] In the present application, formaldehyde is selected as the crosslinking agent. In the complex, polyacrylamide and formaldehyde form a crosslinking structure through covalent bonds, and the amide groups between molecules are crosslinked into an insoluble gel through methylene groups. The crosslinking structure enhances the stability and water resistance of the RTP material, allowing it to swell in water and retain a large volume of water in this swollen state without dissolving. In the present application, the crosslinking degree of the RTP material is changed by increasing the amount of formaldehyde used.
[0072] In the present application, when the amount of formaldehyde is 0.3-0.8% of the molar amount of the complex, the RTP material is slightly cross-linked; when the amount of formaldehyde is 3-8% of the molar amount of the complex, it is highly cross-linked. The water resistance of the slightly cross-linked RTP material is lower than that of the highly cross-linked RTP material. It swells quickly in water and emits phosphorescence for a short time before the phosphorescence disappears. The highly cross-linked RTP material has good water resistance and can emit phosphorescence in water for a long time.
[0073] The present application achieves step-by-step enhancement of phosphorescence through three different constraint methods. The primary constraint is to form a precursor polymer through phosphorescent molecules and acrylamide, which can emit phosphorescence; the precursor is then complexed with cucurbituril 7 to achieve the second constraint, so that the phosphorescence lifetime is enhanced; finally, the complex is cross-linked with formaldehyde as the third constraint, so that the phosphorescence lifetime of the room temperature phosphorescent material is further enhanced, and three different intensities of emission of phosphorescent molecules are achieved.
[0074] In the second aspect, the present application provides a water-resistant room temperature phosphorescent gradient enhancement material. The water-resistant room temperature phosphorescent gradient enhancement material of the present application can effectively hinder molecular motion through covalent bond interactions and host-guest complexation, improve the rigidity of phosphorescent molecules and thus inhibit their non-radiative decay, and the cross-linked structure can shield the quencher, thereby producing efficient polymer room temperature phosphorescent emission. The cross-linked structure enhances the stability and water resistance of the RTP material, and the degree of cross-linking of the RTP material can be changed by increasing the amount of cross-linking agent. The highly cross-linked product can achieve phosphorescent emission in water, and it is still not completely swollen after being immersed in an aqueous solution for 30 minutes, and can still stimulate phosphorescence, and an obvious afterglow can be seen.
[0075] The present application is further described below by way of examples, wherein the examples take the substituent R of the phosphorescent molecule monomer as an example of a carboxyl group.
[0076] Embodiment Synthesize phosphorescent molecular monomers, and the preparation method thereof comprises:
[0077] 498.0 mg of 4-pyridinebenzoic acid was dispersed in 30 mL of anhydrous acetonitrile under ice bath conditions, and 0.6 mL of 4-vinylbenzyl chloride was added after 20 minutes; the ice bath was removed after 5 minutes, stirred with a magnetic stirrer, and heated to 90°C in an oil bath for 24 hours. After the reaction, the reaction liquid was filtered to remove the solid phase, and the liquid phase was dripped into anhydrous ether and recrystallized to obtain a phosphorescent molecular monomer, recorded as PHC, with a molecular weight of 352 and the structural formula as follows:
[0078]
[0079] Example 1
[0080] In 6 mL of anhydrous N,N-dimethylformamide, add 16 mg of azobisisobutyronitrile, 3.52 mg (0.01 mmol) of phosphorescent molecular monomer PHC and 710.2 mg (9.99 mmol) of acrylamide, evacuate and replace with nitrogen three times, copolymerize at 65 ° C for 12 hours to prepare a copolymer. After the reaction, cool to room temperature and filter the reaction solution to obtain a crude solid. The crude solid is dialyzed in deionized water, and the copolymer with a molecular weight cutoff of 3000 to 20000 is retained by a dialysis bag. The solution is freeze-dried and vacuum-dried to obtain an acrylamide-based copolymer.
[0081] The obtained acrylamide-based copolymer and 11.63 mg (0.01 mmol) of cucurbituril 7 were added to water and ultrasonically complexed at 50° C. The solution was freeze-dried and vacuum-dried to obtain a complex.
[0082] 1 g (13.68 mmol) of the complex was dissolved in 3 mL of deionized water, and 25 μL of a 0.1 mol / L hydrochloric acid solution was added for acidification, and nitrogen purging was turned on. Finally, 3.42 mg of a 37% formaldehyde solution was added to the solution and reacted at 60° C. for 12 h. The reaction solution was precipitated with an excess of methanol, and the precipitate was vacuum dried to obtain a water-resistant room temperature phosphorescent gradient enhancement material, which was recorded as phosphorescent material 1.
[0083] Example 2
[0084] The difference between Example 2 and Example 1 is that the dosage of the formaldehyde solution is 91.26 mg, and the rest is the same as Example 1. Example 2 obtains a water-resistant room temperature phosphorescent gradient enhancement material, which is recorded as phosphorescent material 2.
[0085] Example 3
[0086] In 6 mL of anhydrous N,N-dimethylformamide, add 16 mg of azobisisobutyronitrile, 3.52 mg (0.01 mmol) of phosphorescent molecular monomer PHC and 1420.8 mg (19.99 mmol) of acrylamide, evacuate and replace with nitrogen three times, copolymerize at 65 ° C for 12 hours to prepare a copolymer. After the reaction, cool to room temperature and filter the reaction solution to obtain a crude solid. The crude solid is dialyzed in deionized water, and the copolymer with a molecular weight cutoff of 3000 to 20000 is retained by a dialysis bag. The solution is freeze-dried and vacuum-dried to obtain an acrylamide-based copolymer.
[0087] The obtained acrylamide-based copolymer and 4.07 mg (0.0035 mmol) of cucurbituril 7 were added to water and ultrasonically complexed at 50° C. The solution was freeze-dried and vacuum-dried to obtain a complex.
[0088] 1 g (13.68 mmol) of the complex was dissolved in 3 mL of deionized water, and 25 μL of a 0.1 mol / L hydrochloric acid solution was added for acidification, and nitrogen purging was turned on. Finally, 9.12 mg of a 37% formaldehyde solution was added to the solution and reacted at 60° C. for 12 h. The reaction solution was precipitated with excess methanol, and the precipitate was vacuum dried to obtain a water-resistant room temperature phosphorescent gradient enhancement material, which was recorded as phosphorescent material 3.
[0089] Example 4
[0090] In 6 mL of anhydrous N,N-dimethylformamide, add 16 mg of azobisisobutyronitrile, 3.52 mg (0.01 mmol) of phosphorescent molecular monomer PHC and 355.4 mg (5.0 mmol) of acrylamide, evacuate and replace with nitrogen three times, copolymerize at 65 ° C for 12 hours to prepare a copolymer. After the reaction, cool to room temperature and filter the reaction solution to obtain a crude solid. The crude solid is dialyzed in deionized water, and the copolymer with a molecular weight cutoff of 3000 to 20000 is retained by a dialysis bag. The solution is freeze-dried and vacuum-dried to obtain an acrylamide-based copolymer.
[0091] The obtained acrylamide-based copolymer and 19.42 mg (0.0166 mmol) of cucurbituril 7 were added to water and ultrasonically complexed at 50° C. The solution was freeze-dried and vacuum-dried to obtain a complex.
[0092] 1 g of the complex was dissolved in 3 mL of deionized water, and 25 μL of 0.1 mol / L hydrochloric acid solution was added for acidification, and nitrogen purging was turned on. Finally, 34.22 mg of 37% formaldehyde solution was added to the solution and reacted at 60° C. for 12 h. The reaction solution was precipitated with excess methanol, and the precipitate was vacuum dried to obtain a water-resistant room temperature phosphorescent gradient enhancement material, which was recorded as phosphorescent material 4.
[0093] Comparative Example 1
[0094] In 6 mL of anhydrous N,N-dimethylformamide, add 16 mg of azobisisobutyronitrile, 3.52 mg (0.01 mmol) of phosphorescent molecular monomer PHC and 710.2 mg (9.99 mmol) of acrylamide, evacuate and replace with nitrogen three times, copolymerize at 65 ° C for 12 hours to prepare a copolymer. After the reaction, cool to room temperature and filter the reaction solution to obtain a crude solid. The crude solid is dialyzed in deionized water, and the copolymer with a molecular weight cutoff of 3000 to 20000 is retained by a dialysis bag. The solution is freeze-dried and vacuum-dried to obtain an acrylamide-based copolymer.
[0095] 1 g of acrylamide copolymer was dissolved in 3 mL of deionized water, and 25 μL of 0.1 mol / L hydrochloric acid solution was added for acidification, and nitrogen purging was turned on. Finally, 3.2 μL of 37% formaldehyde solution was added to the solution and reacted at 60° C. for 12 h. The reaction solution was precipitated with excess methanol, and the precipitate was vacuum dried to obtain a phosphorescent material, which was recorded as phosphorescent material D1.
[0096] In the present application, in Example 1, the amount of formaldehyde added is 0.3% of the molar amount of the complex; in Example 3, the amount of formaldehyde added is 0.8% of the molar amount of the complex; phosphorescent material 1 and phosphorescent material 3 are lightly cross-linked;
[0097] In the present application, in Example 2, the amount of formaldehyde added is 8% of the molar amount of the complex, and in Example 4, the amount of formaldehyde added is 3% of the molar amount of the complex; the phosphorescent materials 2 and Example 4 are highly cross-linked.
[0098] The phosphorescence performance of the acrylamide-based copolymer, the complex, the phosphorescent material 1, the phosphorescent material 2 and the phosphorescent material D1 prepared in Example 1 was tested by the following method:
[0099] Irradiate the test material with ultraviolet light of wavelength 365nm for 4 seconds, then turn off the light source and observe the fluorescence emission state of the test material.
[0100] Figure 1 The phosphorescence performance diagrams of the acrylamide-based copolymer, complex, phosphorescent material 1 prepared in Example 1 and phosphorescent material D1 prepared in Comparative Example 1. Among them, (a) is the acrylamide-based copolymer prepared in Example 1, (b) is the complex prepared in Example 1, (c) is the phosphorescent material D1 prepared in Comparative Example 1, and (d) is the phosphorescent material 1 prepared in Example 1.
[0101] like Figure 1 As shown in (a), (b) and (d), the naked eye phosphorescence lifetime of the acrylamide-based copolymer, the complex and the phosphorescent material 1 is successively enhanced, among which the slightly cross-linked product of the acrylamide-based copolymer after complexation, i.e. the phosphorescent material 1, has a naked eye phosphorescence lifetime of 5s. Figure 1 As shown in (c) and (d), the uncomplexed slightly cross-linked phosphorescent material D1 is compared with the complexed slightly cross-linked phosphorescent material 1. The phosphorescence lifetime of the phosphorescent material D1 is 3s, and the phosphorescence lifetime of the phosphorescent material 1 is 5s. After complexation, the phosphorescence lifetime of the naked eye is greatly improved.
[0102] The actual pictures of the phosphorescent material 2 prepared in Example 2 before and after drying are as follows: Figure 2 Its phosphorescence properties are shown in Figure 3 As shown. Figure 3 It can be seen that the phosphorescence lifetime of the highly cross-linked phosphorescent material 2 is 5 s, which is the same as the phosphorescence lifetime of the slightly cross-linked phosphorescent material 1 , but its phosphorescence brightness is higher than that of the phosphorescent material 1 .
[0103] The highly cross-linked phosphorescent material 2 of Example 2 was placed in water to test the phosphorescent performance. The test results are as follows: Figure 4 As shown. Figure 4 It can be seen that the phosphorescent emission of the highly cross-linked product phosphorescent material 2 in water is visible to the naked eye and lasts for about 3 seconds. After immersion for 30 minutes, the unswollen part still has phosphorescent emission properties. In theory, a sample of appropriate size can still have phosphorescent emission properties in water even if it is soaked for more than 1 hour as long as there is an unswollen part.
[0104] The phosphorescent material 2 prepared in Example 2 was tested and its phosphorescent lifetime was close to that of the phosphorescent material 1. The phosphorescent material 4 prepared in Example 4 had a phosphorescent lifetime close to that of the phosphorescent material 2 and also had good phosphorescent emission performance in water.
[0105] Although the present application has been described in detail in general terms and in specific embodiments in this specification, it is obvious to those skilled in the art that some modifications or improvements may be made to the present application. Therefore, these modifications or improvements made without departing from the spirit of the present application are within the scope of protection claimed in the present application.
Claims
1. A method for preparing a water-resistant room temperature phosphorescent gradient enhancement material, characterized in that: include: Step 1, preparing phosphorescent molecular monomers; Step 2, dissolving acrylamide in a polar solvent, adding an initiator and a phosphorescent molecular monomer, and copolymerizing under a nitrogen atmosphere; collecting the solid to obtain an acrylamide-based copolymer; Step 3, using cucurbituril or cyclodextrin as the main body and the phosphorescent molecule in the acrylamide copolymer as the guest, performing complexation at 40-50° C. to obtain a complex; Step 4, preparing an aqueous solution of the complex, adding a crosslinking agent to carry out a crosslinking reaction at 50-70° C., and precipitating the reaction solution with a precipitant to obtain a water-resistant room temperature phosphorescent gradient enhancement material; The chemical structure of the phosphorescent molecule monomer is shown in formula (1): Wherein, R is carboxyl, boric acid, amino, cyano, methyl, trifluoromethyl or ethyl formate; The cross-linking agent is formaldehyde.
2. The method for preparing a water-resistant room temperature phosphorescent gradient enhancement material according to claim 1, characterized in that: The preparation method of the phosphorescent molecular monomer is as follows: The phenylpyridine derivative is dissolved in a polar solvent, 4-vinylbenzyl chloride is added, and the mixture is heated to 70-90° C. for reaction, and the liquid phase is collected and recrystallized with a non-polar solvent to obtain a phosphorescent molecular monomer. The chemical structure of the phenylpyridine derivative is shown in formula (2): Wherein, R is carboxyl, boric acid, amino, cyano, methyl, trifluoromethyl or ethyl formate.
3. The method for preparing a water-resistant room temperature phosphorescent gradient enhancement material according to claim 1, characterized in that: The molar ratio of the phosphorescent molecular monomer to acrylamide is 1:(500-2000).
4. The method for preparing a water-resistant room temperature phosphorescent gradient enhancement material according to claim 1, characterized in that: The initiator is azobisisobutyronitrile, azobisdimethylvaleronitrile, ammonium persulfate, potassium persulfate or benzoyl peroxide; The polar solvent is N,N-dimethylformamide, ethanol or acetone.
5. The method for preparing a water-resistant room temperature phosphorescent gradient enhancement material according to claim 1, characterized in that: The molecular weight of the acrylamide-based copolymer is 3,000 to 20,000.
6. The method for preparing a water-resistant room temperature phosphorescent gradient enhancement material according to claim 1, characterized in that: The cucurbituril is cucurbituril 7 or β-cyclodextrin; The molar ratio of the cucurbituril 7 or β-cyclodextrin to the phosphorescent molecule is (1:3) to (5:3).
7. The method for preparing a water-resistant room temperature phosphorescent gradient enhancement material according to claim 1, characterized in that: The dosage of the formaldehyde is 0.3-0.8% of the molar weight of the complex.
8. The method for preparing a water-resistant room temperature phosphorescent gradient enhancement material according to claim 1, characterized in that: The dosage of the formaldehyde is 3-8% of the molar amount of the complex.
9. A water-resistant room temperature phosphorescent gradient enhancement material prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
A method for preparing a pure organic long-life room-temperature phosphorescent polymer material without heavy atoms and amorphous form.
CN109306034B
Room-temperature phosphorescent material based on polymer hydrogen bonds and preparation method thereof
CN110818834A
Room-temperature phosphorescent material based on synergistic effect of polymer and cucurbituril and preparation method thereof
CN111621290A
Preparation method, product and application of room-temperature phosphorescent hydrogel
CN113501974A